Accelerated long-term forgetting in focal epilepsies with special consideration given to patients with diagnosed and suspected limbic encephalitis. (January 2019) - Helmstaedter, Christoph; Winter, Babette; Melzer, Nico; Lohmann, Hubertus; Witt, Juri-Alexander
Abstract: Rationale: Accelerated long-term forgetting (ALF) is a phenomenon found in late onset epilepsy and in transient epileptic amnesia (TEA). Here we evaluated ALF in patients with focal epilepsies and limbic encephalitis (LE) in particular. Methods: ALF was assessed in 36 patients with focal epilepsy and 154 healthy subjects using an extended version of the Verbal Learning and Memory Test (VLMT), with free recall after 30 min and again after one week. From these patients, 89% had temporal lobe epilepsy; 42% left-lateralized; 39% right; 19% bilateral; 17% were diagnosed with hippocampal sclerosis; 64% displayed features indicating LE; 52% with amygdala pathology, and 61% were antibody positive. ALF was defined as either having unimpaired free recall after 30 min and impaired recall after a week (A) or as a loss in recall exceeding the absolute (B) and percentage loss (C) in the interval of the 30 min and one week recall seen in controls by more than one standard deviation. Results: Repeated measures analysis revealed an association between LE and ALF. Depending on its definition (A, B, or C), ALF was evident in 31%, 42%, or 67% of the patients. Poor verbal memory and ALF (C) were prominent in left-lateralized epilepsies. ALF (A) appeared more frequently in auto-antibody negative patients with LE, ALF (B) less frequently with hippocampal sclerosis. Seizures during the interval did not explain ALF. Conclusion: Depending on its definition, ALF is seen in patients with normal or impaired memory at ½ h. ALF seems related to LE but might as well be the first sign of memory impairment in patients with milder epilepsies and not yet definite structural temporal lobe pathology. Longitudinal assessment would be essential for discerning when ALF becomes evident, whether conditions exist in which ALF precedes short-term forgetting, and whether ALF responds to treatment.